Application of Parenting Education Program to Improve Aspects of Cognitive Development - Nurul Fauziah; Siwi Purwanti (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
This study aims to determine the application of parenting education programs among teachers and parents in education units that intend to improve children’s cognitive development. This research uses more descriptive qualitative research. They conducted this research in TK LKMD Catur Tunggal Piyungan with the research source of principals, teachers, and parents. The research data were obtained from interviews using the Google Form or WA application and also document studies. The study results explain that the application of parenting education can improve the cognitive development of early childhood. This is because 1) parents get knowledge related to STPPA or Childhood Development Achievement Level Standard so that the treatment of parents in conducting learning assistance is more conditioned. 2) parents get a way to do learning to children to assist children well, and children get a good stimulus in improving cognitive development.